A rare complication of pre-Eisenmenger patent ductus arteriosus: Pulmonary artery dissection - AY, YASİN; AY, YASİN; KAHRAMAN AY, Nuray; KAHRAMAN AY, NURAY; AYDIN, CEMALETTİN; AYDIN, CEMALETTİN; KARA, İBRAHİM; ZEYBEK, RAHMİ; ZEYBEK, RAHMİ (My University, 2013)
INTRODUCTION: Pulmonary artery dissection associated with patent ductus arteriosus is usually seen in patients with pulmonary hypertension and Eisenmenger-s syndrome. This paper presents a case with pre-Eisenmenger patent ductus arteriosus complicated by pulmonary artery dissection, and explains how she was surgically treated.